William Adolphe Bouguereau note - Bouguereau, William Adolphe, 1825-1905.
Holograph note (Paris; 1878 July 15) signed by Bouguereau in response to a request for his autograph.
Artists.
Collection material in French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Artists